2013
DOI: 10.4014/jmb.1302.02055
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Toxicological Properties of L-Lysine Polymers in CD-1 Mice

Abstract: We recently showed that polylysine, the polymer of lysines, retains anti-prion activity. Although the effectiveness of prion inhibition by polylysine was demonstrated with the regimen tolerated in mice, a determination of quantitative polylysine toxicity is necessary to precisely address the in vivo toxicity level of polylysine. In this communication, we report the results of body weight monitoring and hematologic tests performed in CD-1 mice that received two different tolerable dosages of polylysine for an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Empty polymersomes were further tested for toxicity against NOD/SCID mice. Polylysine is regarded in general as a toxic substance . It is reported that toxicity of polylysine is even dependent on the administration route.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Empty polymersomes were further tested for toxicity against NOD/SCID mice. Polylysine is regarded in general as a toxic substance . It is reported that toxicity of polylysine is even dependent on the administration route.…”
Section: Discussionmentioning
confidence: 99%
“…12 mg kg −1 ) when a single intravenous dose of polylysine with identical molecular masses was given to mice . However Titlow et al reported that polylysine is harmless in mice if administered for a short period. In their study they only observed a transient hypoactivity (sedation) when 8 mg kg −1 of polylysine was administered intraperitoneally for a period of 5 days (a total dose of 40 mg kg −1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds were daily administered intraperitoneally using a 1-mL syringe and a 26-gauge, 1.27-to 2.54-cm (1/2 to 1 inch) needle with a short bevel for 7 days. The injection was made in the lateral aspect of the lower left quadrant [31,32]. The volume injected into each mouse was 10 mL/kg.…”
Section: Inhibition Of Prp Res In Micementioning
confidence: 99%
“…Artificial methods for pLlys synthesis typically yield α-pLlys, since the polymerisation occurs through the α-amino group, and can reach much higher molecular weights than natural ɛ-pLlys. Synthetic pLlys is utilised as an adhesion promoter in cell cultures, and it is being investigated for its antineoplastic activity, anti-prion activity, and gene delivery properties [3][4][5].…”
Section: Introductionmentioning
confidence: 99%